2014
DOI: 10.3390/ijms150711324
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction in Chronic Inflammatory Diseases

Abstract: Chronic inflammatory diseases are associated with accelerated atherosclerosis and increased risk of cardiovascular diseases (CVD). As the pathogenesis of atherosclerosis is increasingly recognized as an inflammatory process, similarities between atherosclerosis and systemic inflammatory diseases such as rheumatoid arthritis, inflammatory bowel diseases, lupus, psoriasis, spondyloarthritis and others have become a topic of interest. Endothelial dysfunction represents a key step in the initiation and maintenance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
299
0
15

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(339 citation statements)
references
References 132 publications
6
299
0
15
Order By: Relevance
“…Indeed, recent research has focused on the link between pain and inflammation, and increased tumor necrosis factor-alfa levels, activation of mitogen-activated protein kinases, and endothelial dysfunction are among inflammatory mechanisms that appear to be shared by psoriasis and migraine. [6][7][8][9][10][11][12]27 Along this line, tumor necrosis factor-alfa inhibition may inhibit pain signaling in experimental arthritis and ameliorate endothelial dysfunction in those with psoriasis and psoriatic arthritis, suggesting the potential for targeted anti-inflammatory pharmacologic therapy in the treatment of migraine. [28][29][30] Only very few studies have to our knowledge reported on the association between psoriasis and migraine.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, recent research has focused on the link between pain and inflammation, and increased tumor necrosis factor-alfa levels, activation of mitogen-activated protein kinases, and endothelial dysfunction are among inflammatory mechanisms that appear to be shared by psoriasis and migraine. [6][7][8][9][10][11][12]27 Along this line, tumor necrosis factor-alfa inhibition may inhibit pain signaling in experimental arthritis and ameliorate endothelial dysfunction in those with psoriasis and psoriatic arthritis, suggesting the potential for targeted anti-inflammatory pharmacologic therapy in the treatment of migraine. [28][29][30] Only very few studies have to our knowledge reported on the association between psoriasis and migraine.…”
Section: Discussionmentioning
confidence: 96%
“…Arterial stiffness is linked to endothelial dysfunction as suggested by the impairment of endothelial vasodilation that always precedes arterial stiffness (Scuteri et al, 2008). Endothelial dysfunction represents a key step in the initiation and maintenance of atherosclerosis and is an independent predictor of cardiovascular events (Steyers and Miller, 2014). Endothelial dysfunction, manifested by a reduction of the endothelium-dependent vasodilation, is associated with the aging process in both the micro and the macrovasculature of animal models (Dal-Ros et al, 2012;Gano et al, 2014;Lakatta and Levy, 2003) and humans Toda, 2012;Walker and Hakkinen, 2014).…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…Since the endothelial cell layer constitutes the primary internal barrier of blood vessels, microvascular endothelial dysfunction is believed to be the initiating process and pathological basis of cardiovascular disease (Ding et al, 2014;Steyers & Miller, 2014;Tousoulis et al, 2014;Hald et al, 2014). Although activated macrophages aggravate endothelial cell injury in hypoxia, the mediator has not been defined (Weldy et al, 2011;Mei et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis and the subsequent vessel destruction are the primary cause of ischemic diseases, such as stroke and coronary heart disease (Schiano et al, 2014;Tano & Gollasch, 2014). Microvascular endothelial dysfunction is believed to be the initiating process and pathological basis of cardiovascular disease (Ding et al, 2014;Steyers & Miller, 2014;Tousoulis et al, 2014).…”
Section: Introductionmentioning
confidence: 99%